Proof of marriage: special measures for war-affected women towards reconciliation - Wijeyesekera, Rose (My University, 2011)
Proof of marriage is necessary to establish legal relationships and benefits such as inheritance rights to property, legitimacy of children, widows’ and orphans’ pension entitlements etc. that supersede marriage. As per the existing laws of Sri Lanka, marriage can be proved by documentary evidence of registration of marriage and/or of performance of recognized customary rites. Though registration is not mandatory for non-Kandyan marriages, it has almost become so in practice. People have lost lives, property and also documentary evidence of entitlements and relationships as a result of war. The widows/widowers and children, of those who have died/disappeared during or immediately after the war, may also have lost documentary evidence to establish their legal relationships that enable them to claim the afore-mentioned rights and entitlements. Most of the dead/disappeared being male, women, both as widows and as mothers, have become destitute, and their inability to establish marriage makes them even more vulnerable. In this context, application of the same rules/standards of law to this marginalized group would further discriminate them. Hence, the situation calls for positive legal and administrative measures to guarantee equal protection of the law to those who have been disadvantaged due to social and political causes. The proposed article addresses the kind of affirmative action that should be taken within the existing national and international legal/policy standards, to ease the burden of proof of marriage of this group, thus guaranteeing them equality. Key words: proof or marriage, affirmative action, war-affected wome